Perencanaan Lanskap di Desa Wisata Guliang Kangin Kabupaten Bangli - Monikaria, Dwi; Sukewijaya, I Made; Yusiana, Lury Sevita (Jurnal Arsitektur Lansekap, 2024)
Landscape Planning of the Tourism Village Area in Guliang Kangin Tourism Village, Bangli Regency. Guliang Kangin Tourism Village is a tourist village located in Bangli Regency. This tourist village has a lot of potential that can be developed into a tourist attraction. Guliang Kangin Tourism Village requires landscape planning in accordance with its potential and constraints. Such planning can be done by developing tourism potential. This research method uses a survey method with research stages namely inventory, analysis, synthesis, concept, and planning. The basic concept of this planning uses the concept of length of stay as the development of tourism potential in general related to the development of tourist attractions and tourist facilities in Guliang Kangin Tourism Village. The final result of this planning is a site plan of tourist attractions and facilities in Guliang Kangin Tourism Village.